2003
DOI: 10.1364/oe.11.003041
|View full text |Cite
|
Sign up to set email alerts
|

Poling of a channel waveguide

Abstract: This paper describes thermal poling of a silica based channel waveguide Mach-Zehnder interferometer, and direct measurent of the dc-Kerr and induced electro-optic coefficients. A /(3) of 5.2 (+/-0.4) x 10-22 (m/V)2 was measured for the un-poled waveguide, and r-coefficient of approximately 0.07 pm/V was induced by poling. /(3) increased by a factor of 1.9 after poling. It is shown that the dc-Kerr effect plays an important role in the poled device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
9
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
9
0
2
Order By: Relevance
“…3. A change in χ (3) by a factor 2-4 has been reported by several groups [8,9], but in our measurements the coefficient 3πLχ (3) / λn 0 increased only marginally (~20%). After poling the parabola is translated by the recorded field E rec .…”
Section: Characterization Through the Measured Phase Shiftsupporting
confidence: 50%
“…3. A change in χ (3) by a factor 2-4 has been reported by several groups [8,9], but in our measurements the coefficient 3πLχ (3) / λn 0 increased only marginally (~20%). After poling the parabola is translated by the recorded field E rec .…”
Section: Characterization Through the Measured Phase Shiftsupporting
confidence: 50%
“…This is because the optical nonlinearity in glasses, which may be smaller than that in crystals, appears in substantial magnitudes in fibers, 1,2 waveguides, [3][4][5] and microspheres 6 due to long propagation distances. In addition, the nonlinearity can be continuously changed by varying glass composition.…”
mentioning
confidence: 99%
“…waveguides, [3][4][5] and microspheres 6 due to long propagation distances. In addition, the nonlinearity can be continuously changed by varying glass composition.…”
mentioning
confidence: 99%
“…However, there are reports of third-order nonlinear susceptibility modification after poling inside the nonlinear region. [2][3][4] To our best knowledge, this phenomenon has only been observed in planar waveguides and optical fibers, due to the measurement techniques employed.…”
mentioning
confidence: 99%
“…12 Recently, Kashyap has reported that the ͑3͒ susceptibility can be modified by a factor of 2 due to a modification of electronic clouds of bonds under the local electric field. 3 The modification of the ͑3͒ susceptibility after thermal poling is still under discussion since the results which are published varies from group to group: for example, no modification of the ͑3͒ has been reported in Refs. 14 and 15, but has been found to increase by a factor close to two in fibers.…”
mentioning
confidence: 99%